2015
DOI: 10.3748/wjg.v21.i43.12361
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus NS5A promotes insulin resistance through IRS-1 serine phosphorylation and increased gluconeogenesis

Abstract: Taken together, our results suggest the role of HCV NS5A in the induction of insulin resistance by modulating various cellular targets involved in the insulin signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Both fat accumulation and hepatosteatosis have been related to elevations of serum aminotransferase levels in HCV infections rather than DM. It has been reported that nonstructural protein 5A (NS5A) encoded by the HCV RNA genome is involved in insulin receptor substrate-1 (IRS-1) phosphorylation and regulates the insulin signaling pathway [3]. In addition, NS5A transfected cells, decreased the levels of serin phosphorylation that facilitate gluconeogenesis, and inhibited the synthesis of glycogen.…”
Section: Discussionmentioning
confidence: 99%
“…Both fat accumulation and hepatosteatosis have been related to elevations of serum aminotransferase levels in HCV infections rather than DM. It has been reported that nonstructural protein 5A (NS5A) encoded by the HCV RNA genome is involved in insulin receptor substrate-1 (IRS-1) phosphorylation and regulates the insulin signaling pathway [3]. In addition, NS5A transfected cells, decreased the levels of serin phosphorylation that facilitate gluconeogenesis, and inhibited the synthesis of glycogen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in vertebrates have shown that the expression of some genes encoding metabolic enzymes increases significantly during a viral infectious process (Kuo et al., ; Parvaiz et al., ). Nevertheless, little is known about the specific molecular mechanisms affecting the metabolism of key enzymes involved in energy metabolism in shrimp species by viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in vertebrates have shown that the expression of some genes encoding metabolic enzymes increases significantly | 5591 during a viral infectious process (Kuo et al, 2014;Parvaiz et al, 2015 (Chen et al, 2011). Subsequently, Su et al (2014) found a significant increase in several markers of various meta- suggested by the inhibition of PK (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that HCV infection can cause insulin resistance by the phosphorylation of IRS-1 at a serine residue (Ser307) followed by a decreased phosphorylation of Akt Thr(308), Fox01 Ser(256) and GSK3β Ser(9), downstream players in the insulin signaling pathway[72,73]. These data raise the question whether insulin resistance is the cause of liver steatosis in patients with chronic HCV infection, or the consequence of viral molecular expression.…”
Section: Insulin Resistance and Hcv Infectionmentioning
confidence: 99%